2015
DOI: 10.4081/ijas.2015.3302
|View full text |Cite
|
Sign up to set email alerts
|

Meat Quality of Lambs Fed Different Saltbush Hay (Atriplex Nummularia) Levels

Abstract: Climate changes have increased soil and water salinity, compromising animal production especially in dry areas where scientists have become more interested in halophyte plants, like saltbush. The effects of saltbush hay levels (30, 40, 50 and 60%) were evaluated based on physical-chemical, nutritional and sensory parameters of Santa Inês lamb meat. Thirty-two 8-month-old castrated Santa Inês lambs, with initial weights of 22±1.97 kg were used; they were slaughtered after 60 days in the feedlot. The pH, colour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 50 publications
1
13
1
Order By: Relevance
“…Carcass adiposity measures from salicornia-fed camels were noticeably higher than those measures from Rhodes grass-fed camels. This was in contrast with the results reported by Al-Owaimer et al (2008) and Moreno et al (2015), who reported that animals fed halophytes had a tendency to have a higher lean and a lower fat content. The discrepancy in results may be related to the differences in halophyte species, stage of animal maturity, animal species, halophyte concentration in diet, and concentration of energy intake.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Carcass adiposity measures from salicornia-fed camels were noticeably higher than those measures from Rhodes grass-fed camels. This was in contrast with the results reported by Al-Owaimer et al (2008) and Moreno et al (2015), who reported that animals fed halophytes had a tendency to have a higher lean and a lower fat content. The discrepancy in results may be related to the differences in halophyte species, stage of animal maturity, animal species, halophyte concentration in diet, and concentration of energy intake.…”
Section: Discussioncontrasting
confidence: 57%
“…Utilizing halophytes and other salt-tolerant plants in the ration of ruminants is a feasible solution to minimize the problems of feed and water shortage in desert, saline coastal, and subcoastal areas (Al-Shorepy et al, 2010;Moreno et al, 2015). Salicornia (Salicornia bigelovii Torr) has been considered as one of the most salt-tolerant species among the halophytes and has been shown to maintain normal growth even when soil NaCl concentration exceeds 1.3 M, two times greater than full-strength seawater salinity (Kong and Zheng, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…However, Moreno et al (2015) showed that the water holding capacity was 11% higher in the meat of lambs fed diets with saltbush but did not affect the meat pH or cooking weight loss.…”
Section: Effect Of Saline Water On Meat Qualitymentioning
confidence: 89%
“…Small ruminants use water efficiently because of their small size, optimal utilization of ingested water (Araújo, Voltolini, Chizzoti, Turco, & Carvalho, 2010;Kumar, Singh, Kumar, Sahoo, Naqvi, 2016. ), ability to retain water and excrete dry stools and concentrated urine, high tolerance to water stress (Silva, Araújo, Oliveira, Azevedo, & Furtado, 2016), and tolerance to foods with high salt concentrations (Moreno et al, 2015;Castro et al, 2017) and high salinity water (Moura et al, 2016;Yousfi, Marques, Betti, Araus, & Serret, 2016). Potter (1968) reported that the consumption of high salinity water by sheep might increase the osmotic pressure in the rumen, without affecting the ruminal microbiota, and change the heart and respiratory rate of the animals (Duarte et al, 2014).…”
Section: Introductionmentioning
confidence: 99%